Tam iz powrotem - Wójcik, Wojciech (Poland : WFDiF ; CANAL +, 2002)
The story of the Polish “robbery of the century”. Lodz, 1965: a well-respected doctor with an anti-communist record wants to leave the country for England where his wife and daughter are. He meets an old acquaintance from the days of the anti-communist struggle who needs a partner in a robbery. It is the only way to get enough money to buy a passport and start a new life in the West, and he promises that the attack on a bank vehicle transporting money can be done without spilling blood. Trumped up charges brought by a secret police agent who wants to destroy the doctor’s career make it easier for him to decide. The robbery is successful, but one of the drivers gets shot. He is taken to the hospital for an operation. The surgeon is the very person who took part in the robbery. He has to decide whether the only witness should survive. This is the first feature film made by a director of a popular criminal television series.
Duration: 01:42:00
Keywords: Fiction films